The largest emission sector direly needs more research funds to clean-up - Jose, Rajan; Ramakrishna, Seeram (Springer, 2024)
Biomass growing and harvesting; mineral and fossil resource extraction; and processing of materials, fuels and food accounted for more than 55% of global greenhouse gas emissions in 2022 and more than 60% if land-use change impacts are considered” reports the international resource panel in their 2024 global resource outlook (United Nations Environmental Program 2024). In a nutshell, material sourcing and processing for all walks of life contributed 55% of the global emission. An inadvertent surge in material usage by 60% than the 2022 levels is predicted (United Nations Environmental Program 2024); if the current habits of sourcing and processing prevail, the future of a liveable planet Earth is uncertain. The report also notes that “the scientific community has never been more aligned before or more resolute on the need for urgent global transformation towards the sustainable use of resources” (United Nations Environmental Program 2024); however, practical changes are yet to be seen. Obviously, switching into a circular economy and circular use of materials are unanimously opined as the way forward for a sustainable planet. Circular economy, by definition, is an intentionally designed economic system wherein life means are made cyclic, similar to natural life cycle, such that resources are not wasted or accumulated in air, soil, or water but avoid adverse health effects on humans as well as other living beings (An Introduction to Circular Economy 2021). Circular materials, on the other hand, are “renewable materials” or “sustainable materials” or “low-carbon materials” that foster a healthy living environment and a circular economy via the elimination or reduction of associated greenhouse gas emissions and resource depletion and wastage (Ramakrishna and Jose 2022). Circular materials are purposely designed with lower environmental footprint and social costs and higher circularity potential while satisfying the cost as well as functional requirements. The primary purpose of the Springer Nature journal Materials Circular Economy is to promote and direct circular materials research for sustainability.